IDEOLOGICAL AMBIGUITIES AND CONFLICT OF IDEOLOGY IN REPRESENTATIONS OF WOMEN IN SELECTED AFRICAN FEMALE AND MALE NOVELS - HOUNDJO, THÉOPHILE; ALLAGBE, Akinlola Monday (My University, 2018)
The political ideology of women‟s movements like feminism, womanism, Stiwanism, African feminism and others is to redress the power imbalances between men and women through advocacy of women‟s rights. But the fact that some women ill-treat their fellow women and even girl children creates ideological ambiguities and conflict of ideology in the political ideology they advocate for. This article focuses on ideology of womanism and radical feminism so as to unfold some causes of ideological ambiguities and conflict of ideology in the representations of women in Lola Shoneyin‟s The Secret Lives of Baba Segi’s Wives and Asare Adei‟s A Beautiful Daughter. The result reveals that social injustice, pride, egoism, revenge and malice make women go against the brainchild of their ideology. The above problems make women enter into conflict with one another and even abuse children. In a nutshell, it is discovered that ideological ambiguities and conflict of ideology have made women expose themselves and their fellow women to men‟s violence and status quo.
Keywords: Ideology; ambiguity; women; conflict; womanism; radical feminism.